ANALISA KERUSAKAN PERKERASAN JALAN MENURUT METODE BINA MARGA DAN PCI (PAVEMENT CONDITION INDEX) SERTA ALTERNATIF PENANGANANNYA ( STUDI KASUS RUAS JALAN PAHLAWAN BUKIT RAYA - TENGGARONG SEBERANG, KAB.KUTAI KARTANEGARA - PRAMONO, PUGUH (KURVA S JURNAL MAHASISWA, 2018)
The highway is an important facility for the community to be able to achieve a goal that they want, for that the community needs a safe and convenient highway for its users, and is expected to increase the industry and the economy of the community. But over time the road will experience a decline in conditions according to the increasing age of the road so that it will become an obstacle in the smooth running of a trip. Pahlawan Street uses a Flexible Pavement system, with some road bodies already using AC-BC surface layer and AC-WC, which are around the Hero's path. The length of the road to be studied is Â± 10 KM, which at this time at some point in the damaged condition will be the cause of the damage to the road to find a good solution to overcome the damage. The stages of analysis in writing this thesis are by conducting an LHR survey, visual survey at the research location, determining the type and level of damage and measuring the dimensions of damage which includes the length, width and damage that occurs, calculating the area of damage, analyzing the surface damage conditions of the Build City Road - Gusik by calculating the PCI value and the overall Road Condition value using the Pavement Condition Index (PCI) method and the Bina Marga (1990) method. The results of the analysis based on the data obtained from the field survey shows that the value of road conditions or ratting given by Pavement Condition Index (PCI) is 79.79 for the overall average based on the PCI rating between 71 to 85 in very good condition and the value given by Bina Marga is 11.48 based on the priority value of the clan between 1 to 10, then routine maintenance is carried out.